Isolation and identification of Steroids from Different Parts of Prosopis Cineraria - Preeti Khandelwal (Journal of Global Pharma Technology, 2017)
Prosopis cineraria are a tree of remarkable importance and a rich source of secondary metabolites. The present study was carried out to investigate the steroid content present in the leaves, stem and pods of Prosopis cineraria. The method of Tomita et al., was used for isolation of steroids. The structure of the isolated compound was established on the basis of physical and chemical test and spectroscopic evidences (TLC, IR and GC- MS). The study concluded that a single type of steroid Diosgenin was found in all the parts of the selected plant species.Keywords: Prosopis cineraria; Steroids; Diosgenin; Thin Layer Chromatography.